Gradient structure nanofiber membrane with lithium extraction and power generation functions and preparation method thereof

CN122682564BActive Publication Date: 2026-10-20WUHAN TEXTILE UNIV +1
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202611172385.9
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2026-08-04
Publication Date
2026-10-20
Estimated Expiration
2046-08-04

AI Technical Summary

Technical Problem

该系统虽能完成镁锂分离与锂离子浓缩,但整体以膜分离与蒸发工艺为主,未引入选择性吸附功能层,锂离子吸附容量与选择性有限;同时仅实现锂资源单一回收,无法同步实现锂离子吸附与能源收集,功能集成度低

Benefits of technology

在本申请的技术方案中,通过将乙烯-乙烯醇共聚物纳米纤维与锂离子筛混合,涂覆于多孔无纺布基材表面,得到复合纳米纤维膜,再将单壁碳纳米管分散液涂覆于复合纳米纤维膜表面,单壁碳纳米管表面富含的羧基和羟基之间的氢键作用进行自组装,上层的单壁碳纳米管在纳米纤维膜材料表面形成了一种蜘蛛网状结构,从而得到本申请的兼具提锂和发电功能的梯度结构纳米纤维膜。该膜材料依靠锂离子筛的晶体结构实现锂离子高效捕获,不依赖于物理的尺寸筛分与道南效应截留。同时,纳米纤维形成的多孔结构可提高离子传输速率,减少孔道堵塞与传质阻力,提升提锂效率与运行稳定性。此外,该兼具提锂和发电功能的梯度结构纳米纤维膜通过在复合纳米纤维膜层涂覆单壁碳纳米管分散液,并在膜两端连接电极,构建出连续稳定的导电通道,使该膜在吸附锂离子的同时,可利用离子定向迁移实现同步发电,将提锂过程与能源回收一体化,提高能源利用率,且该材料经多次吸附和解吸循环后仍维持较高的锂离子吸附容量,具备良好的可重复使用性。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122682564B_ABST
    Figure CN122682564B_ABST
Patent Text Reader

Abstract

The application provides a gradient structure nanofiber membrane with lithium extraction and power generation functions and a preparation method thereof, and belongs to the field of nanofiber materials. The preparation method of the gradient structure nanofiber membrane comprises the following steps: dispersing nanofibers in an isopropyl alcohol solution to form a nanofiber suspension; adding lithium ion sieves into the suspension and fully mixing to obtain a mixed solution; coating the mixed solution on the surface of a porous non-woven fabric substrate to form a composite nanofiber membrane; and coating a single-walled carbon nanotube dispersion on the composite nanofiber membrane to obtain the gradient structure nanofiber membrane with lithium extraction and power generation functions. The nanofiber membrane is prepared by compounding nanofibers with lithium ion sieves and further loading a single-walled carbon nanotube dispersion on the upper layer, so that the gradient structure nanofiber membrane material has high lithium ion adsorption capacity and stable ion transmission channels. Therefore, the nanofiber membrane realizes multifunctional integration of lithium ion adsorption and synchronous power generation, and can be repeatedly used for lithium extraction.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of nanofiber materials technology, specifically to a gradient structure nanofiber membrane with both lithium extraction and power generation functions, and its preparation method. Background Technology

[0002] With the rapid development of the global new energy industry, lithium resources, as a core component of power batteries and energy storage, have made efficient and green extraction technologies a key factor restricting the sustainable development of the new energy industry. my country has abundant reserves of salt lake brine resources, but they generally suffer from low lithium-ion concentrations and high levels of impurity ions such as magnesium, sodium, and calcium. Meanwhile, traditional lithium extraction processes such as precipitation and solvent extraction suffer from long processes, high energy consumption, poor selectivity, and environmental pollution, making it difficult to achieve efficient separation and extraction of lithium resources from brine.

[0003] More significantly, traditional lithium extraction technologies only achieve the recycling of lithium resources and cannot capture and convert the potential energy in brine, such as ion concentration differences and interfacial potential differences. The entire process is characterized by low energy efficiency and high energy consumption, which does not align with the modern industrial development trend of low-carbon, energy-saving, green, and efficient production. Although new technologies such as membrane separation and selective adsorption are currently applied to brine lithium extraction, they generally suffer from insufficient ion selectivity, poor extraction efficiency, and poor reusability. Furthermore, most existing lithium extraction membrane materials are single-function, only capable of adsorbing and intercepting lithium ions without introducing conductive components to construct efficient ion transport channels, making it impossible to generate electricity simultaneously with lithium extraction, resulting in energy waste. In addition, the performance of most adsorption materials rapidly degrades after multiple adsorption-desorption cycles, making stable and reusable operation difficult.

[0004] While related technologies utilize nanofiltration membrane separation, multi-stage reverse osmosis membrane concentration, and solar evaporation to enrich and purify lithium ions in brine, these systems, though capable of separating magnesium and lithium and concentrating lithium ions, primarily rely on membrane separation and evaporation processes without introducing a selective adsorption functional layer. This results in limited lithium ion adsorption capacity and selectivity. Furthermore, they only achieve single-function lithium resource recovery, failing to simultaneously realize lithium ion adsorption and energy harvesting, leading to low functional integration. In the field of membrane materials for efficient lithium extraction, existing technologies also exhibit significant shortcomings: membrane layers only possess single functions of separation or concentration, lacking conductive components and electrodes, thus failing to achieve synergistic functions of lithium ion adsorption and simultaneous power generation. Moreover, these materials are prone to deformation and insufficient mechanical strength in high-salinity brine systems, easily leading to structural damage and performance degradation during long-term operation, making it difficult to meet the requirements of industrial-scale stability, high efficiency, and reusability. Summary of the Invention

[0005] In view of the technical problems existing in the background art, this application provides a gradient structure nanofiber membrane with both lithium extraction and power generation functions and its preparation method. The gradient structure nanofiber membrane with both lithium extraction and power generation functions has high lithium ion adsorption capacity and stable conductive channels, which can realize simultaneous lithium extraction and power generation, and has strong stability and can be reused.

[0006] To achieve the above objectives, in a first aspect, this application provides a method for preparing a gradient-structured nanofiber membrane that combines lithium extraction and power generation functions, comprising: We provide dispersions of nanofibers, alcohol solutions, porous nonwoven fabric substrates, lithium-ion sieves, and single-walled carbon nanotubes. Nanofibers were dispersed in an alcohol solution to obtain a nanofiber suspension; After adding lithium-ion sieves to the nanofiber suspension and mixing, a mixture is obtained; The mixture was coated onto a porous nonwoven fabric substrate and dried to obtain a composite nanofiber membrane. A single-walled carbon nanotube dispersion was coated onto a composite nanofiber membrane to obtain a gradient structure nanofiber membrane that combines lithium extraction and power generation functions; wherein the surface of the single-walled carbon nanotubes includes at least one of hydroxyl and carboxyl functional groups.

[0007] Furthermore, the nanofibers include at least one of ethylene-vinyl alcohol copolymer, polyvinyl alcohol, polyethylene oxide, and high-density polyethylene; and / or, Lithium-ion sieves include at least one of titanium-based lithium-ion sieves and manganese-based lithium-ion sieves; and / or, The porous nonwoven fabric substrate includes at least one of polypropylene nonwoven fabric, polylactic acid nonwoven fabric, glass fiber nonwoven fabric and polyester nonwoven fabric.

[0008] Furthermore, the mass fraction of nanofibers in the nanofiber suspension is 0.5%-5%.

[0009] Furthermore, the mass fraction of lithium ion sieve in the mixture is 0.5%-10%, and the mass ratio of lithium ion sieve to nanofiber is (0.5-5):1.

[0010] Furthermore, the alcohol solution comprises deionized water and alcohol in a volume ratio of (1-5):1.

[0011] Furthermore, the alcohol includes at least one of isopropanol, methanol, ethanol, n-butanol, and ethylene glycol.

[0012] Furthermore, the mass fraction of single-walled carbon nanotubes in the single-walled carbon nanotube dispersion is 0.1%-10%.

[0013] Furthermore, coating processes include spraying, lamination, scraping, or spin coating.

[0014] Secondly, this application also provides a gradient structure nanofiber membrane that combines lithium extraction and power generation functions, prepared by the preparation method of the gradient structure nanofiber membrane that combines lithium extraction and power generation functions described in any of the above claims.

[0015] The beneficial effects of this application are as follows: In the technical solution of this application, ethylene-vinyl alcohol copolymer nanofibers are mixed with lithium-ion sieves and coated onto the surface of a porous nonwoven fabric substrate to obtain a composite nanofiber membrane. Then, a single-walled carbon nanotube dispersion is coated onto the surface of the composite nanofiber membrane. The carboxyl and hydroxyl groups on the surface of the single-walled carbon nanotubes undergo self-assembly through hydrogen bonding, forming a spiderweb-like structure on the surface of the nanofiber membrane material. This results in the gradient structure nanofiber membrane of this application, which combines lithium extraction and power generation functions. This membrane material achieves efficient lithium-ion capture based on the crystal structure of the lithium-ion sieve, independent of physical size sieving and Donald effect retention. Simultaneously, the porous structure formed by the nanofibers improves the ion transport rate, reduces pore blockage and mass transfer resistance, and enhances lithium extraction efficiency and operational stability. Furthermore, this gradient structure nanofiber membrane, which combines lithium extraction and power generation functions, constructs a continuous and stable conductive channel by coating a single-walled carbon nanotube dispersion onto the composite nanofiber membrane layer and connecting electrodes at both ends of the membrane. This allows the membrane to generate electricity simultaneously by utilizing the directional migration of ions while adsorbing lithium ions, thus integrating the lithium extraction process with energy recovery and improving energy utilization. Moreover, the material maintains a high lithium ion adsorption capacity even after multiple adsorption and desorption cycles, demonstrating good reusability.

[0016] The above description is only an overview of the technical solution of this application. In order to better understand the technical means of this application and to implement it in accordance with the contents of the specification, and to make the above and other objects, features and advantages of this application more obvious and understandable, the following are specific embodiments of this application. Attached Figure Description

[0017] To more clearly illustrate the technical solutions of this application, the accompanying drawings used in this application will be briefly described below. Obviously, the drawings described below are merely some embodiments of this application. For those skilled in the art, other drawings can be obtained from these drawings without any creative effort.

[0018] Figure 1 This is a physical image of the gradient structure nanofiber membrane with both lithium extraction and power generation functions from Example 1. Figure 2 SEM image of the polypropylene porous nonwoven fabric of Example 1; Figure 3 This is a SEM image of the ethylene-vinyl alcohol copolymer nanofiber suspension composite lithium ion sieve from Example 1. Figure 4 This is a SEM image of the gradient structure nanofiber membrane with both lithium extraction and power generation functions in Example 1. Figure 5 The bar chart shows the adsorption capacity after lithium extraction of the gradient structure nanofiber membrane with both lithium extraction and power generation functions in Example 1. Figure 6 The output voltage and current curves of the gradient structure nanofiber membrane with both lithium extraction and power generation functions in Example 1 when placed under xenon lamp irradiation and using C / Zn asymmetric electrodes during the lithium extraction process; Figure 7 The output voltage and current curves of the gradient structure nanofiber membrane with both lithium extraction and power generation functions in Example 1 when it is placed under xenon lamp irradiation at different temperatures and a C / Zn asymmetric electrode is used during the lithium extraction process. Figure 8 The output current and voltage of the gradient structure nanofiber membrane with both lithium extraction and power generation functions in Example 1 when it is placed under xenon lamp irradiation at different temperatures and a C / Zn asymmetric electrode is used during the lithium extraction process. Figure 9 The voltage and current curves of the gradient structure nanofiber membrane with both lithium extraction and power generation functions in Example 1 when it was placed under xenon lamp irradiation at different humidity levels and a C / Zn asymmetric electrode was used during the lithium extraction process. Figure 10 The output voltage and current of the gradient structure nanofiber membrane with both lithium extraction and power generation functions in Example 1 when it is placed under xenon lamp irradiation at different humidity levels and C / Zn asymmetric electrode is used during the lithium extraction process; Figure 11 The output voltage and current curves of the gradient structure nanofiber membrane with both lithium extraction and power generation functions in Example 1 when placed in different solutions under xenon lamp irradiation and using C / Zn asymmetric electrodes during the lithium extraction process; Figure 12 The output voltage and current of the gradient structure nanofiber membrane with both lithium extraction and power generation functions in Example 1 when placed in different solutions under xenon lamp irradiation and using C / Zn asymmetric electrodes during the lithium extraction process; Figure 13 The output voltage and current of the gradient structure nanofiber membrane with both lithium extraction and power generation functions in Example 1 when it is placed under xenon lamp irradiation and different electrodes are used during the lithium extraction process; Figure 14 The charging performance and energy storage of two series-connected gradient structure nanofiber membranes with both lithium extraction and power generation functions were tested on a multi-capacity capacitor. Figure 15 Four tandem gradient structure nanofiber membranes, which combine lithium extraction and power generation functions, were tested as a power source to power a small light bulb. Detailed Implementation

[0019] The embodiments of the technical solution of this application will now be described in detail with reference to the accompanying drawings. These embodiments are only used to more clearly illustrate the technical solution of this application and are therefore merely examples, and should not be used to limit the scope of protection of this application.

[0020] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by one of ordinary skill in the art to which this application pertains; the terminology used herein is for the purpose of describing particular embodiments only and is not intended to limit the application; the terms “comprising” and “having”, and any variations thereof, in the specification, claims, and foregoing description of the drawings are intended to cover non-exclusive inclusion.

[0021] In this document, the term "embodiment" means that a particular feature, structure, or characteristic described in connection with an embodiment may be included in at least one embodiment of this application. The appearance of this phrase in various places throughout the specification does not necessarily refer to the same embodiment, nor is it a separate or alternative embodiment mutually exclusive with other embodiments. It will be explicitly and implicitly understood by those skilled in the art that the embodiments described herein can be combined with other embodiments.

[0022] The "range" disclosed in this application is defined by a lower limit and an upper limit. A given range is defined by selecting a lower limit and an upper limit, which define the boundaries of a particular range. Ranges defined in this way can include or exclude endpoints and can be arbitrarily combined; that is, any lower limit can be combined with any upper limit to form a range. For example, if ranges of 60-120 and 80-110 are listed for a specific parameter, it is expected that ranges of 60-110 and 80-120 are also included. Furthermore, if minimum range values ​​of 1 and 2 are listed, and if maximum range values ​​of 3, 4, and 5 are listed, then the following ranges are all expected: 1-3, 1-4, 1-5, 2-3, 2-4, and 2-5. In this application, unless otherwise stated, the numerical range "ab" represents a shortened representation of any combination of real numbers between a and b, where a and b are real numbers. For example, the numerical range "0-5" indicates that all real numbers between "0-5" have been listed in this article; "0-5" is simply a shortened representation of these numerical combinations. Furthermore, when a parameter is stated as an integer ≥2, it is equivalent to disclosing that the parameter is, for example, an integer such as 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, etc.

[0023] Unless otherwise specified, all embodiments and optional embodiments of this application can be combined to form new technical solutions.

[0024] Unless otherwise specified, all technical features and optional technical features of this application may be combined to form new technical solutions.

[0025] Unless otherwise specified, the terms "comprising" and "including" as used in this application are open-ended. For example, "comprising" and "including" may mean that other components not listed may also be included or contained.

[0026] In the description of the embodiments in this application, the term "and / or" is merely a description of the relationship between related objects, indicating that three relationships can exist. For example, A and / or B can represent: A existing alone, A and B existing simultaneously, and B existing alone. Additionally, the character " / " in this document generally indicates that the preceding and following related objects have an "or" relationship.

[0027] The embodiments of this application will be described in further detail below with reference to the accompanying drawings and examples. The detailed description of the following embodiments and the accompanying drawings are used to illustrate the principles of this application by way of example, but should not be used to limit the scope of this application, that is, this application is not limited to the described embodiments.

[0028] To address the technical problems of poor ion selectivity, limited functionality, insufficient material stability, and low energy utilization efficiency in lithium extraction technology, this application provides, in a first aspect, a method for preparing a gradient structure nanofiber membrane that combines lithium extraction and power generation functions, comprising: We provide dispersions of nanofibers, alcohol solutions, porous nonwoven fabric substrates, lithium-ion sieves, and single-walled carbon nanotubes. Nanofibers were dispersed in an alcohol solution to obtain a nanofiber suspension; After adding lithium-ion sieves to the nanofiber suspension and mixing, a mixture is obtained; The mixture was coated onto a porous nonwoven fabric substrate and dried to obtain a composite nanofiber membrane. A single-walled carbon nanotube dispersion was coated onto a composite nanofiber membrane to obtain a gradient structure nanofiber membrane that combines lithium extraction and power generation functions; wherein the surface of the single-walled carbon nanotubes includes at least one of hydroxyl and carboxyl functional groups.

[0029] In the technical solution of this application, ethylene-vinyl alcohol copolymer nanofibers are mixed with lithium-ion sieves and coated onto the surface of a porous nonwoven fabric substrate to obtain a composite nanofiber membrane. Then, a single-walled carbon nanotube dispersion is coated onto the surface of the composite nanofiber membrane. The carboxyl and hydroxyl groups on the surface of the single-walled carbon nanotubes undergo self-assembly through hydrogen bonding, forming a spiderweb-like structure on the surface of the nanofiber membrane material. This results in the gradient structure nanofiber membrane of this application, which combines lithium extraction and power generation functions. This membrane material achieves efficient lithium-ion capture based on the crystal structure of the lithium-ion sieve, independent of physical size sieving and Donald effect retention. Simultaneously, the porous structure formed by the nanofibers improves the ion transport rate, reduces pore blockage and mass transfer resistance, and enhances lithium extraction efficiency and operational stability. Furthermore, this gradient structure nanofiber membrane, which combines lithium extraction and power generation functions, constructs a continuous and stable conductive channel by coating a single-walled carbon nanotube dispersion onto the composite nanofiber membrane layer and connecting electrodes at both ends of the membrane. This allows the membrane to generate electricity simultaneously by utilizing the directional migration of ions while adsorbing lithium ions, thus integrating the lithium extraction process with energy recovery and improving energy utilization. Moreover, the material maintains a high lithium ion adsorption capacity even after multiple adsorption and desorption cycles, demonstrating good reusability.

[0030] It can be explained that the gradient structure nanofiber membrane, which has both lithium extraction and power generation functions, consists of a porous non-woven fabric substrate, nanofibers, lithium ion sieves, and a spider web structure conductive network formed by single-walled carbon nanotubes from bottom to surface. The coating process can be a step-by-step coating process using spraying, doctor blade or spin coating.

[0031] It can be explained that the gradient structure nanofiber membrane, which combines lithium extraction and power generation functions, consists of a porous nonwoven fabric substrate, nanofibers, lithium-ion sieves, and single-walled carbon nanotubes from bottom to surface. The fiber diameter of the porous nonwoven fabric substrate at the bottom is 1μm-10μm, the fiber diameter of the nanofibers is 100nm-1000nm, and the diameter of the spider web structure fiber formed by the single-walled carbon nanotubes is 10nm-50nm. The diameter increases layer by layer at the bottom, which has a certain capillary effect, which is conducive to water absorption and ion transport, and can improve the adsorption capacity and power generation function of the nanofiber membrane.

[0032] It can be explained that nanofibers are dispersed in an alcohol solution to obtain a nanofiber suspension, wherein the dispersion method includes, but is not limited to, high-speed shearing or high-pressure homogenization.

[0033] It can be explained that the gradient structure nanofiber membrane, which combines lithium extraction and power generation functions, can improve the output voltage and current by setting metal electrodes on the membrane side. The active metal electrodes include at least one of copper, zinc and aluminum.

[0034] It is understandable that the coating process used to coat the mixture onto the porous nonwoven fabric substrate is the same as the coating process used to coat the single-walled carbon nanotube dispersion onto the composite nanofiber membrane.

[0035] In some embodiments, the nanofibers include at least one of ethylene-vinyl alcohol copolymer, polyvinyl alcohol, polyethylene oxide, and high-density polyethylene.

[0036] Specifically, ethylene-vinyl alcohol copolymers are used to prepare nanofibers. These materials have hydrophilic hydroxyl groups in their molecules, allowing for uniform dispersion of lithium ions. The materials are easy to mold, possess good mechanical toughness, and the interwoven fibers form a three-dimensional network structure, facilitating brine penetration and ensuring sufficient contact between the adsorbent and lithium ions. Polyvinyl alcohol is also used to prepare nanofibers. Its excellent hydrophilic properties allow for the fabrication of highly porous, high-absorption-rate fiber membranes. Its surface polarity allows for uniform lithium ion attachment, while its heat resistance and high strength promote lithium salt dissociation, providing smooth migration channels for lithium ions and increasing the total lithium adsorption capacity of the membrane. High-density polyethylene is also used to prepare nanofibers, providing the membrane with excellent mechanical strength and acid / alkali chemical stability, while simultaneously creating a porous structure to ensure smooth flow of brine and ions.

[0037] In some embodiments, the lithium-ion screen includes at least one of titanium-based lithium-ion screens and manganese-based lithium-ion screens.

[0038] Specifically, spinel-type lithium titanate from titanium-based ion sieves was selected as the lithium-ion sieve. The spinel structure of spinel-type lithium titanate is robust and can form three-dimensional channels, which can improve the cycle stability and acid and alkali resistance of the nanofiber membrane and maintain structural stability during repeated adsorption and desorption. Manganese-based lithium-ion sieves were selected as the lithium-ion sieve. Manganese-based lithium-ion sieves have stronger visible light absorption capabilities, which can work synergistically with the surface carbon nanotube photothermal layer to enhance the photothermal conversion effect, accelerate the migration rate of ions in the interlayer channels, and simultaneously improve the lithium adsorption rate and power generation capacity of the membrane material.

[0039] In some embodiments, the porous nonwoven fabric substrate includes at least one of polypropylene nonwoven fabric, polylactic acid nonwoven fabric, glass fiber nonwoven fabric, and polyester nonwoven fabric.

[0040] In this embodiment, polypropylene nonwoven fabric has low cost and lightweight properties; polylactic acid nonwoven fabric improves flexibility and thermal adhesion; polyester nonwoven fabric has high temperature resistance and stability; and glass fiber nonwoven fabric has temperature resistance, flame retardancy, and thermal stability. The above-mentioned substrates can be selected according to actual conditions to provide different performance improvements for the nanofiber membrane.

[0041] In some embodiments, the mass fraction of nanofibers in the nanofiber suspension is 0.5%-5%.

[0042] In this embodiment, the mass fraction of nanofibers in the nanofiber suspension is set to 0.5%-5%, which makes the nanofiber suspension fluid and processable. During the film formation process, a continuous and porous three-dimensional network structure is formed, so that the nanofiber membrane has suitable mechanical strength and structural stability while having high porosity and specific surface area. This provides sufficient attachment sites and supporting framework for lithium ion sieves and single-walled carbon nanotube dispersions, thereby improving the lithium adsorption capacity and power generation efficiency of the nanofiber membrane.

[0043] In some embodiments, the mass fraction of lithium ion sieve in the mixture is 0.5%-10%, and the mass ratio of lithium ion sieve to nanofiber is (0.5-5):1.

[0044] In this embodiment, the mass fraction of lithium ion sieves in the mixture is set to 0.5%-10%, which allows the lithium ion sieves to be dispersed in the nanofiber suspension and uniformly dispersed in the three-dimensional skeleton of the nanofiber membrane, thereby increasing the adsorbent loading and contact area per unit area of ​​the membrane and improving the lithium extraction adsorption efficiency of the nanofiber membrane.

[0045] In this embodiment, the mass ratio of lithium-ion sieve to nanofiber is set to (0.5-5):1, which makes the density of lithium-ion sieve anchored to nanofiber appropriate, providing sufficient solid-liquid contact area and adsorption capacity, and the nanofiber can provide sufficient mechanical support and flexibility, thereby enabling the gradient structure nanofiber membrane to realize lithium extraction and power generation functions.

[0046] In some embodiments, the alcohol solution comprises deionized water and alcohol in a volume ratio of (1-5):1.

[0047] In this embodiment, the volume ratio of deionized water to isopropanol is set to (1-5):1. The mixed solution at this ratio has moderate polarity and surface tension, which can effectively disperse ethylene-vinyl alcohol copolymer nanofibers and produce a moderate micro-swelling effect on the surface of nanofibers. This is beneficial for the subsequent anchoring and penetration of nanofiber suspension or functional coating on the substrate surface, thereby enabling the nanofiber membrane to achieve lithium extraction and power generation functions.

[0048] In some embodiments, the alcohol includes at least one of isopropanol, methanol, ethanol, n-butanol, and ethylene glycol.

[0049] In this embodiment, any one or more of the above-mentioned alcohols are selected. These alcohol molecules have both hydrophilic hydroxyl groups and hydrophobic alkyl chains, and have low surface tension suitable for polypropylene porous nonwoven fabric substrates. They can be mixed with deionized water in any proportion to adjust the polarity of the mixed solution, and can also wet and unclog the micropores of polypropylene and dissolve and remove residual release agents on the surface of nonwoven fabrics. Alcohols with different carbon chain lengths and molecular structures can flexibly control the degree of micro-swelling of nanofibers, adapt to the penetration and anchoring requirements of different coating slurries, ensure the stable composite molding of functional adsorption layer and conductive layer, and enable the final membrane material to simultaneously possess the dual performance of long-term lithium extraction and power generation.

[0050] In some embodiments, the mass fraction of single-walled carbon nanotubes in the single-walled carbon nanotube dispersion is 0.1%-10%.

[0051] In this embodiment, the mass fraction of single-walled carbon nanotubes in the single-walled carbon nanotube dispersion is set to 10%, which can form a continuous and uniform photothermal and conductive network in the nanofiber membrane, maintain good dispersibility, reduce agglomeration, and not block the pores of the nanofiber membrane, thereby improving power generation efficiency and not affecting the lithium ion adsorption performance of the nanofiber membrane.

[0052] In some embodiments, the coating process includes spraying, laying, scraping, or spin coating.

[0053] In this embodiment, spray coating, by atomizing the suspension and depositing it onto the substrate surface, offers advantages such as uniform coating, adaptability to complex substrate morphologies, and controllable thickness. Film laying involves attaching a pre-formed nanofiber membrane to the substrate surface via hot pressing or bonding, ensuring controllable functional layer thickness without introducing additional solvents, thus reducing chemical damage or swelling to the substrate. Wafer coating uses a doctor blade and roller to directly apply the suspension to the substrate and dry it into a film, offering simplicity and high efficiency. Spin coating involves dropping the suspension onto the substrate surface, relying on centrifugal force generated by high-speed rotation to evenly spread the slurry; this process requires minimal suspension, minimizes raw material loss, and is fast and efficient. The above composite processes can be selected based on actual conditions; all four methods can yield gradient-structured nanofiber membranes with both lithium extraction and power generation functions.

[0054] Secondly, this application also provides a gradient structure nanofiber membrane that combines lithium extraction and power generation functions. This gradient structure nanofiber membrane is prepared by any of the aforementioned technical solutions using the preparation method of a gradient structure nanofiber membrane that combines lithium extraction and power generation functions. This gradient structure nanofiber membrane that combines lithium extraction and power generation functions has all the beneficial effects of the aforementioned preparation method of a gradient structure nanofiber membrane that combines lithium extraction and power generation functions, and will not be elaborated further here.

[0055] The following are some specific embodiments. It should be noted that the embodiments described below are exemplary and are only used to explain this application, and should not be construed as limiting this application. Where specific techniques or conditions are not specified in the embodiments, they shall be performed in accordance with the techniques or conditions described in the literature in this field or according to the product instructions. Reagents or instruments whose manufacturers are not specified are all conventional products that can be obtained commercially.

[0056] I. Preparation Method Example 1 We provide ethylene-vinyl alcohol copolymers, isopropanol solutions, polypropylene nonwoven fabrics, spinel-type lithium titanate ion sieves, and single-walled carbon nanotube dispersions. 2g of ethylene-vinyl alcohol copolymer was dispersed in isopropanol and deionized water (volume ratio of isopropanol to deionized water was 1:1) to obtain a nanofiber suspension. 2g of spinel-type lithium titanate ion sieve was added to 200mL of nanofiber suspension and mixed to obtain a mixture. 202 mL of the mixture was coated onto the surface of a 20×20 cm polypropylene nonwoven fabric, and after drying, a composite nanofiber membrane was obtained. 16.5 mL of single-walled carbon nanotube dispersion was coated onto the surface of the composite nanofiber membrane to obtain the gradient structure nanofiber membrane of Example 1, which has both lithium extraction and power generation functions.

[0057] Example 2 Compared with Example 1, the only difference is that polyvinyl alcohol is used instead of ethylene-vinyl alcohol copolymer, and lithium titanate is used instead of spinel-type lithium titanate ion sieve. The remaining steps are the same as in Example 1 and will not be repeated here. The gradient structure nanofiber membrane with lithium extraction and power generation functions of Example 2 is obtained.

[0058] Example 3 Compared with Example 1, the only difference is that polyethylene oxide is used instead of ethylene-vinyl alcohol copolymer, and polyolefin nonwoven fabric is used instead of polypropylene nonwoven fabric. The remaining steps are the same as in Example 1, and will not be repeated here. The gradient structure nanofiber membrane with lithium extraction and power generation functions of Example 3 is obtained.

[0059] Example 4 Compared with Example 1, the only difference is that high-density polyethylene is used instead of ethylene-vinyl alcohol copolymer, and glass fiber nonwoven fabric is used instead of polypropylene nonwoven fabric. The remaining steps are the same as in Example 1, and will not be repeated here. The gradient structure nanofiber membrane with lithium extraction and power generation functions of Example 4 is obtained.

[0060] Example 5 Compared with Example 1, the only difference is that graphene powder is used instead of single-walled carbon nanotubes. The remaining steps are the same as in Example 1 and will not be repeated here. The resulting gradient structure nanofiber membrane with both lithium extraction and power generation functions is an example 5.

[0061] Example 6 Compared with Example 1, the only difference is that conductive carbon black is used instead of single-walled carbon nanotubes. The remaining steps are the same as in Example 1 and will not be repeated here. The resulting gradient structure nanofiber membrane with both lithium extraction and power generation functions is the one described in Example 6.

[0062] Comparative Example 1 Compared with Example 1, the only difference is that the polypropylene nonwoven fabric is removed and glass is used as the substrate. The mixture is coated on the surface of the glass substrate and dried to obtain a composite nanofiber membrane. 16.5 mL of single-walled carbon nanotube dispersion is coated on the surface of the composite nanofiber membrane, dried and peeled off. The remaining steps are the same as in Example 1 and will not be repeated here. The gradient structure nanofiber membrane of Comparative Example 1 is obtained.

[0063] Comparative Example 2 Compared with Example 1, the only difference is the removal of the ethylene-vinyl alcohol copolymer, which will not be described in detail here, resulting in the gradient structure nanofiber membrane of Comparative Example 2.

[0064] Comparative Example 3 Compared with Example 1, the only difference is the removal of the spinel-type lithium titanate ion sieve, which will not be described in detail here, resulting in the gradient structure nanofiber membrane of Comparative Example 3.

[0065] Comparative Example 4 Compared with Example 1, the only difference is the removal of single-walled carbon nanotubes, which will not be described in detail here, resulting in the gradient structure nanofiber membrane of Comparative Example 4.

[0066] II. Testing Methods Current and voltage detection method: A gradient-structured nanofiber membrane with both lithium extraction and power generation functions was cut into 1cm × 6cm pieces. PVC wires were clipped together to carbon electrodes and zinc electrodes on both sides of the membrane. One half of the 1cm × 6cm gradient-structured nanofiber membrane with the zinc electrode was placed in 20mL of brine, while the other half with the carbon electrode was irradiated under a xenon lamp with a constant current power supply. The wires connecting the two electrodes were then connected to a semiconductor analyzer (KEITHLEY). The instrument could read the current and voltage data. The xenon lamp irradiation time was 2 hours, and the semiconductor analyzer monitored the current and voltage changes in real time during the lithium extraction process. Experimental conditions: Temperature: 25℃; Humidity: 45%; Ions in the brine used: Na+ + K + Li + Ion concentration in the brine used: Na +103.86 g / L, K + 6.895 g / L, Li + 2.02 g / L; Electrode type: C-Zn electrode (carbon-zinc electrode); Electrode area: 5 mm × 5 mm; Wire type: PVC wire.

[0067] Lithium adsorption capacity testing method: A gradient-structured nanofiber membrane with both lithium extraction and power generation functions was cut into 1cm × 6cm pieces. Acid elution was performed using a 0.2mol / L hydrochloric acid solution (30mL) for 4 hours. The lithium ion concentration after elution was then measured. Lithium ion concentration was quantitatively detected using an inductively coupled plasma optical emission spectrometer (ICP-OES) with an Agilent 5800. Instrument operating parameters were: RF power 1200W, plasma gas flow rate 14L / min, nebulizer gas flow rate 0.7L / min, lithium detection line 670.784nm, and three parallel tests were performed with the average value. The test environment was constant temperature 20℃-25℃, humidity 40%-60%, and the plasma channel was protected with argon gas; air isolation was not required. Sample pretreatment: The acid elution solution was filtered and diluted with ultrapure water. A standard curve was established using a gradient lithium standard solution. The lithium concentration value was output by the instrument, and the lithium adsorption capacity of the membrane material was calculated.

[0068] Cyclic Lithium Extraction Test: A gradient-structured nanofiber membrane with both lithium extraction and power generation functions was cut into 1cm × 6cm pieces. Half of the membrane was placed in 20mL of brine, and the other half was irradiated under a xenon lamp with a constant current power supply for 2 hours. After irradiation, the membrane was eluted in 30mL of 0.2mol / L hydrochloric acid solution for 4 hours. 10mL of the eluent was collected and the lithium-ion concentration was measured using inductively coupled plasma optical emission spectrometry (ICP-OES). The membrane was then removed from the eluent and soaked in 50mL of deionized water for 30 minutes. After drying in an oven for 10 minutes, the lithium extraction process was repeated. The process was repeated 11 times: first, the membrane was irradiated in brine with a xenon lamp for 2 hours, then eluted in hydrochloric acid solution, and 10mL of the eluent was collected to measure the lithium-ion concentration. The membrane was then soaked in water and dried. The process was repeated for each lithium extraction cycle. Experimental conditions were identical for each cycle: temperature: 25℃; humidity: 45%; ion species in the brine: Na. + K + Li + Ion concentration in the brine used: Na + 103.86 g / L, K + 6.895 g / L, Li + : 2.02 g / L; membrane area: 1 cm × 6 cm; brine volume: 20 mL; eluent concentration: 0.2 mol / L hydrochloric acid solution; eluent volume: 30 mL; oven temperature: 60 ℃.

[0069] III. Analysis of Test Results for Each Embodiment and Comparative Example Table 1 shows the test data for Examples 1-6 and Comparative Examples 1-4. The current values ​​in the table are attached. Figure 6 The values ​​are taken at a time of 120 minutes, and the voltage values ​​are attached. Figure 6 The value when the time is 120 minutes.

[0070] By comparing Examples 1-6 and Comparative Examples 1-4, it can be seen that the current and voltage of Examples 1-6 are all higher than those of Comparative Examples 1-4. The adsorption capacity of Comparative Example 4 is similar to that of Examples 1-6, but the current and voltage of Comparative Example 4 are much lower than those of Examples 1-6, indicating that Comparative Example 4 does not have the function of generating electricity. Examples 1-6, on the other hand, have both high adsorption capacity and power generation function. By coating the composite nanofiber membrane with a single-walled carbon nanotube dispersion and connecting electrodes at both ends of the membrane, a continuous and stable conductive channel is constructed. This allows the membrane to generate electricity simultaneously by utilizing the directional migration of ions while adsorbing lithium ions, integrating the lithium extraction process with energy recovery, improving energy utilization. Moreover, the material maintains a high lithium ion adsorption capacity after multiple adsorption and desorption cycles, demonstrating good reusability.

[0071] From the appendix Figure 5 As shown in the attached figure, this is the lithium-ion capacity test result of the gradient structure nanofiber membrane of this application after 11 adsorption-acid elution-desorption cycles. All capacity data were obtained by collecting the desorption hydrochloric acid solution in each cycle and converting it to lithium-ion concentration using an Agilent 5800 ICP-OES instrument. The lithium desorption capacity of the membrane remained stable in the first 5 cycles. When the number of cycles increased to 6-11, the adsorption capacity only decreased slightly, without any sudden performance degradation. These experimental results fully demonstrate that the gradient structure nanofiber membrane exhibits outstanding overall cycle durability, meeting the practical requirements for long-term continuous lithium extraction from salt lake brine. Furthermore, the parallel sample error is small, the test data has high repeatability, and the technical effect is well-supported by data.

[0072] From the appendix Figure 6As shown in the attached figure, this is a real-time monitoring curve of the open-circuit voltage and short-circuit current changing over time during a 2-hour photothermal lithium extraction experiment using the gradient nanofiber membrane of this application. The black curve represents the open-circuit voltage, and the red curve represents the short-circuit current. Initially, a lithium-ion concentration gradient rapidly forms between the brine and the membrane layer. Under the photothermal effect of the carbon nanotubes, ions migrate rapidly, and the voltage and current rise rapidly. After 40 minutes, the system reaches a dynamic equilibrium of ion transport, and the voltage and current remain stable after a slight increase. The gradient membrane of this application can simultaneously generate stable electrical energy while adsorbing and extracting lithium, achieving integrated lithium extraction and power generation. The electrical signal shows no attenuation after 2 hours of continuous operation, the membrane's layered structure is stable, and its long-term power generation performance is excellent. The photothermal conversion of the carbon nanotubes accelerates lithium-ion migration and improves the overall power output.

[0073] From the appendix Figure 7 and attached Figure 8 It can be seen that the current gradually increases with increasing temperature. This is because the increased temperature accelerates the ion migration rate, effectively increasing the potential difference of the system. (See attached...) Figure 9 and attached Figure 10 It can be seen that when the relative humidity is in the range of 25%–75%, the output voltage and current of the device remain generally stable. Specifically, the gradient structure nanofiber membrane maintains a voltage of 0.79V and a current of 325μA under moderate humidity (55%RH) conditions. (See attached image) Figure 11 and attached Figure 12 Experiments were conducted on the substrate solution types for the gradient structure nanofiber membrane of this application, and attached... Figure 13 Comparative experiments were conducted on the electrode materials external to the gradient nanofiber membrane of this application, confirming that the gradient nanofiber membrane possesses good environmental adaptability. Crucially, replacing the carbon electrode with an active metal electrode improved the voltage and current output of the device. This improvement is because the active metal electrode can continuously generate ions through redox reactions, promoting directional ion migration, thereby increasing the ion current density and ultimately optimizing power generation performance.

[0074] Appendix Figure 14 Using the two series-connected gradient nanofiber membranes of this application as a power source, constant current / constant voltage charging tests were conducted on capacitors of different capacities to evaluate their energy storage performance. The charging curves exhibited a typical RC exponential charging law. As the capacitance increased from 470μF to 4700μF, the energy storage process of the capacitor slowed down, and the charging time increased from 117 seconds to 696 seconds. At the same time, due to the limitation of the power supply output voltage characteristics, the final stable charging voltage decreased slightly with the increase of capacitance (from 1.32V to 1.20V), proving that the gradient nanofiber membrane of this application has power generation function in practical applications and can provide power to other devices.

[0075] Appendix Figure 15Using the four series-connected gradient nanofiber membranes of this application as a power source, a light bulb was lit up. As shown in the figure, the light bulb was successfully lit, proving that the gradient nanofiber membrane of this application has the function of generating electricity. The gradient nanofiber membrane generates current through ion migration caused by the ion concentration difference.

[0076] It should be noted that this application is not limited to the above-described embodiments. The above embodiments are merely examples, and any embodiments with the same structure and effect as the technical concept within the scope of this application are included in the technical scope of this application. Furthermore, various modifications that can be conceived by those skilled in the art to the embodiments, and other ways of constructing by combining some of the constituent elements of the embodiments, without departing from the spirit of this application, are also included in the scope of this application.

Claims

1. A method for preparing a gradient-structured nanofiber membrane with both lithium extraction and power generation functions, characterized in that, include: We provide dispersions of nanofibers, alcohol solutions, porous nonwoven fabric substrates, lithium-ion sieves, and single-walled carbon nanotubes. The nanofibers are dispersed in the alcohol solution to obtain a nanofiber suspension; The lithium-ion sieve is added to the nanofiber suspension and mixed to obtain a mixture; The mixture is coated onto the porous nonwoven fabric substrate, and after drying, a composite nanofiber membrane is obtained. The single-walled carbon nanotube dispersion is coated onto the composite nanofiber membrane to obtain a gradient structure nanofiber membrane with both lithium extraction and power generation functions; wherein, the surface of the single-walled carbon nanotube includes at least one of hydroxyl and carboxyl functional groups.

2. The method for preparing a gradient structure nanofiber membrane with both lithium extraction and power generation functions according to claim 1, characterized in that, The nanofibers include at least one of ethylene-vinyl alcohol copolymer, polyvinyl alcohol, polyethylene oxide, and high-density polyethylene; and / or, The lithium-ion screen includes at least one of titanium-based lithium-ion screens and manganese-based lithium-ion screens; and / or... The porous nonwoven fabric substrate includes at least one of polypropylene nonwoven fabric, polylactic acid nonwoven fabric, glass fiber nonwoven fabric, and polyester nonwoven fabric.

3. The method for preparing a gradient structure nanofiber membrane with both lithium extraction and power generation functions according to claim 1, characterized in that, The nanofiber suspension contains 0.5%-5% nanofibers by mass.

4. The method for preparing a gradient structure nanofiber membrane with both lithium extraction and power generation functions according to claim 1, characterized in that, The mass fraction of lithium ion sieve in the mixture is 0.5%-10%, and the mass ratio of lithium ion sieve to nanofiber is (0.5-5):

1.

5. The method for preparing a gradient structure nanofiber membrane with both lithium extraction and power generation functions according to claim 1, characterized in that, The alcohol solution comprises deionized water and alcohol, wherein the volume ratio of the deionized water to the alcohol is (1-5):

1.

6. The method for preparing a gradient structure nanofiber membrane with both lithium extraction and power generation functions according to claim 5, characterized in that, The alcohol includes at least one of isopropanol, methanol, ethanol, n-butanol, and ethylene glycol.

7. The method for preparing a gradient structure nanofiber membrane with both lithium extraction and power generation functions according to claim 1, characterized in that, The mass percentage of single-walled carbon nanotubes in the single-walled carbon nanotube dispersion is 0.1%-10%.

8. The method for preparing a gradient structure nanofiber membrane with both lithium extraction and power generation functions according to claim 1, characterized in that, The coating process includes spraying, film laying, scraping, or spin coating.

9. A gradient-structured nanofiber membrane that combines lithium extraction and power generation functions, characterized in that, The gradient structure nanofiber membrane with both lithium extraction and power generation functions is prepared by the method described in any one of claims 1-8.

Citation Information

Patent Citations

  • Reverse electrodialysis-driven forward osmosis plateau salt lake lithium extraction system and working method thereof

    CN121405200A

  • Lithium manganate conductive material and preparation method thereof

    CN121518826A